Analysis of Shopping Cart in Retail Companies Using Apriori Algorithm Method and Model Profset - permatasari, putri agung (International Journal of Engineering and Emerging Technology, 2020)
This research needed a priori algorithm method to produce association rules, with a "if-then" pattern. Apriori algorithm uses an iterative approach known as level-wise search, where k-groups of products are used to explore (k + 1) product groups or (k + 1) -itemset (Han and Kamber, 2001). A priori algorithm method is expected to provide vacancy information on one of the stock items that are often purchased simultaneously by the customer. Product optimization is carried out using the profset model, which evaluates the profit margins generated per product and is developed to maximize cross-selling opportunities. Based on this background, research will be conducted under the title Shopping Cart Analysis in Retail Companies Using the Apriori Algorithm Method and Model Profset